2017
DOI: 10.1158/1541-7786.mcr-16-0322
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Relevance of Tumor Purity and Interaction with MGMT Methylation in Glioblastoma

Abstract: Promoter methylation status of O-6-methylguanine-DNA methyltransferase (MGMT), a DNA repair enzyme, is a critical biomarker in glioblastoma (GBM), as treatment decisions and clinical trial inclusion rely on its accurate assessment. However, interpretation of results is complicated by poor interassay reproducibility as well as a weak correlation between methylation status and expression levels of MGMT. This study systematically investigates the influence of tumor purity on tissue subjected to MGMT analysis. A q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 40 publications
(39 reference statements)
4
15
0
Order By: Relevance
“…For all pathological variables, histology demonstrated the highest importance in LGGs, and purity index for GBMs. Our results indicated that glioma purity has great value in predicting the prognosis, which was also pointed out by other researchers [24][25][26] but is not widely used.…”
Section: Discussionsupporting
confidence: 52%
“…For all pathological variables, histology demonstrated the highest importance in LGGs, and purity index for GBMs. Our results indicated that glioma purity has great value in predicting the prognosis, which was also pointed out by other researchers [24][25][26] but is not widely used.…”
Section: Discussionsupporting
confidence: 52%
“…The tumor microenvironment does not only include tumor cells but also infiltrated immune cells, fibroblasts, and stromal cells comprising the tumor volume [35]. Several studies suggested that lower tumor purity is frequently linked to aggressive characteristics [26, 36]. In this study, we found that both the immune and stromal scores were positively correlated to the ADAMTSL4 expression, suggesting that ADAMTSL4 could reflect the increased fraction of immune and stromal cells.…”
Section: Discussionsupporting
confidence: 51%
“…This was clearly shown by Patel and colleagues who demonstrated that pure IDH1 wild-type proneural tumors were associated with a better survival compared to highly heterogeneous proneural tumors containing cells with other subtypes [21]. Similarly, tumor purity was recently shown to be an important parameter to determine a positive association of MGMT methylation with patient survival [17]. We show that ZBTB18 attenuates the expression of genes associated with EMT and with time-to-tumor progression in glioblastoma [36, 37].…”
Section: Discussionmentioning
confidence: 95%
“…The DNA repair gene O-6-methylguanine-DNA methyltransferase ( MGMT ) is one such gene for which promoter methylation has been shown to result in gene silencing in many cancers [15-17]. …”
Section: Introductionmentioning
confidence: 99%